2019 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2019
DOI: 10.1109/vr.2019.8797854
|View full text |Cite
|
Sign up to set email alerts
|

Ad-hoc Study on Soldiers Calibration Procedure in Virtual Reality

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…VR devices will not fully replace traditional equipment, but can serve as a more affordable alternative for training. Researchers Greunke and Sadagic (2016), and Taupiac et al (2019) have validated that the effect of VR training is comparable to the actual training in some cases, for example, for improving the proficiency of some military equipment usage.…”
Section: Military Trainingmentioning
confidence: 98%
See 2 more Smart Citations
“…VR devices will not fully replace traditional equipment, but can serve as a more affordable alternative for training. Researchers Greunke and Sadagic (2016), and Taupiac et al (2019) have validated that the effect of VR training is comparable to the actual training in some cases, for example, for improving the proficiency of some military equipment usage.…”
Section: Military Trainingmentioning
confidence: 98%
“…VR training applications are typically created according to specific tasks characterized by a fixed procedure and a practical purpose for a specific training target. Thus their implementations are generally miscellaneous and different from each other (Lang et al, 2018;Si et al, 2018;Taupiac et al, 2019). Xie et al (2006) explored generalized descriptions of different training scenarios.…”
Section: Creation Pipeline Of Vr Training Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that skills gained in virtual simulations may be successfully transferred to real life situations [42,53] and retained over a longer period of time [10]. Accordingly, virtual reality has been applied to training and learning in a broad spectrum of domains including industrial processes and security [38,40], aviation safety [10], cultural heritage [3,4], military training [54,69], Internet of Things [77] surgery [1,59,65,71], geography [39], safety procedures [10], and social interactions [36,37,64,72,73]. Virtual reality has also been widely applied to education and a thorough survey of the research in such broad area is outside the scope of this paper.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, several results show that skills gained in such simulations are transferable to real life situations [45], [59] and are retained over a longer period of time [14]. Some existing applications provide training for firefighting [15], [16], [78], military purposes [60], [76], industrial processes [44], helping teachers deal with disruptive behaviors [41], [82], surgery [3], [65], [74], [81], safety procedures [14], and dealing with stressful situations [40], [73].…”
Section: A Virtual Reality In Educationmentioning
confidence: 99%